DETERMINATION AND STUDY OF THE VOLUME AND DENSITY OF COMPLEX POROUS SAMPLES - Kulbek , М.; Dzhaksigeldinova, Э. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Various porous materials are widely used in various industries, such as chemical, metallurgical, energy, light, food, etc. Therefore, a comprehensive study of their structure and physical and technical properties is of great scientific and technological importance. The article presents the results of determining and studying the volume and density of porous sample materials using a new experimental method. The determination of the volume and density of waterproof samples of any complex shape can be easily determined on the basis of Archimedes ' law. However, it is impossible to determine the volume and density of porous water-absorbing samples of complex shape directly using this law. The article presents new experimental methods (methods) for determining the volume and density of such porous samples of complex shape. The results of experimental work carried out using the proposed new methods are presented and analyzed.